MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PROGRAM RABAT BETON JALAN PEDESAAN: Increasing Community Participation In Rural Road Concrete Rebate Program - Aminullah, Aminullah; Subrata, I Gusti Made; Ramli, Ramli; Ardika, Gede Tusan; Titawati, Titin; Seventilofa, I Gusti Ngurah Octova; Pasti, I Wayan (Yayasan Al-Amin Qalbu, 2023)
The aim of implementing this service is to increase community participation in the rural road concrete rebate program. Implementation methods include deliberation, inventory and preparation of needs, implementation and assistance with concrete rebates. The concrete rebate program for village roads was implemented with the participation of the local community. The local community also has environmental awareness, but is more enthusiastic and aware of the importance of cooperation in making the village program a success after deliberations were held between the village government, residents and the team from the university. The concrete rebate begins with inventory and preparation of needs, then continues with the implementation of the rebate with the initial steps, namely leveling the surface of the road to be rebated, installing mall wood for the boundaries and size of the rebate, installing iron and starting the rebate or concreting. The preparation and implementation process can be carried out due to the participation and self-help of the local community, so it can be said that the community really participates in the concrete rebate program